PEACE-EXPERIENCE IN RELIGIONS - Kadankavil, Thomas (Journal of Dharma, 1986)
There is something mystical about peace that one naturally desires to experience it as one becomes aware of it. The idea of peace has been associated with the virtue ofjustice which when realized in its full measure would beget peace. Justice is not an easy concept to define. One of the earliest attempts to define it is found in Plato’s Republic: the discussion starts with the definition put forward by Simonides, "That to give back what is owed to each is just." Thrasymachos gives the definition that justice is whatever suits the strongest. In this sense, for him, even injustice also would be virtuous. Against this view Socrates takes the position that justice is a value for its own sake. In the second Book of the Republic he suggests that the nature of justice is more easily to be discovered in the macrocosm, the State, than in the microcosm, the individual. A well-ordered society enables each person to deyote himself to the task he is best fitted for, and this guarantees peace in the state. Applying the concept of order of classes in the society to the soul, Socrates defines justice as the due arrangement of the three elements-gold, silver and iron-in their proper stations in the soul namely that the reasoning part rules, with its auxiliary spirited part, over the desiring part. In Plato the highest truth of all, which underlies justice and all other virtues is the idea of the good, the guiding star of the soul, and end of the philosopher’s study. Only the soul of the just seeks Supreme Good which generates Supreme wisdom, happiness and peace. Thus, the central philosophy of the Republic is built upon the concept of Justice, which ultimately brings supreme peace and happiness.